Deactivation of ATP-Binding Cassette Transporters ABCB1 and ABCC1 Does Not Influence Post-ischemic Neurological Deficits, Secondary Neurodegeneration and Neurogenesis, but Induces Subtle Microglial Morphological Changes - Manrique-Castano, Daniel; Sardari, Maryam; Silva de Carvalho, Tayana; Doeppner, Thorsten R.; Popa-Wagner, Aurel; Kleinschnitz, Christoph; Chan, Andrew; Hermann, Dirk M. (Frontiers in Cellular Neuroscience, 2019)
ATP-binding cassette (ABC) transporters efficiently prevent the access of pharmacological compounds to the ischemic brain, thereby impeding the efficacy of stroke therapies. ABC transporters can be deactivated by selective inhibitors, which potently increase the brain accumulation of drugs. Concerns have been raised that long-term ABC transporter blockade may promote neurodegeneration and compromise neurological recovery. To elucidate this issue, we exposed male C57BL/6 mice to transient intraluminal middle cerebral artery occlusion and examined the effects of the selective ABCB1 inhibitor tariquidar (8 mg/kg/day) or ABCC1 inhibitor MK-571 (10 mg/kg/day), that were administered alone or in combination with each other over up to 28 days. Reproducible motor-coordination deficits were noted in ischemic mice by neurological score, RotaRod, tight rope and open field tests over 42 days, which were not influenced by ABCB1, ABCC1 or combined ABCB1 and ABCC1 deactivation. Brain and striatum volume, and corpus callosum thickness were not altered by ABCB1, ABCC1 or combined ABCB1 and ABCC1 deactivation. Similarly, neuronal survival, astroglial scar formation and microglial response evaluated by NeuN, GFAP and Iba-1 immunohistochemistry were unchanged. Endogenous neurogenesis, assessed by BrdU incorporation analysis, was not influenced. Our data could not detect any detrimental effects of long-term ABC transporter deactivation post-ischemia. Our data raise the question whether the clinical use of ABC transporter inhibitors has prematurely been abandoned.